Asymptotic analysis of flow processes at drawing of single optical microfibres - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Fujimoto Meinecke, Ken; Rauh, Cornelia; Delgado, Antonio (International Journal of Chemical Reactor Engineering, 2011)
Microstructured optical fibres (i.e. fibres that contain holes) have assumed a high profile in recent years, and given rise to many novel optical devices. The problem of manufacturing such fibres by heating and then drawing a preform is considered for both the cases of annular microfibres and annular capillaries. A fluid-mechanics model suggested in literature that uses asymptotic analysis based on the small aspect ratio of capillaries is analysed and revised. The leading-order equations are examined in some asymptotic limits, many of which give valuable practical information about the control parameters that influence the drawing process. Additionally, the solution obtained for a single capillary provides a suitable basis for describing more complicated fibre structures. Copyright © 2011 The Berkeley Electronic Press. All rights reserved.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.asympt
Keywords: asymptotic analysis; holey fibre; microstructured optical fibres; numerical efforts; photonic crystal fibres

Comparison between an analytical asymptotic fiber drawing model with full Navier-Stokes solution taking into account the effects of inner pressure and surface tension - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Fujimoto Meinecke, Ken; Rauh, Cornelia; Delgado, Antonio (Journal of Lightwave Technology, 2011)
A fluid-mechanics model that make use of asymptotic analysis based on small aspect ratio of capillaries has been compared with the full 3-D set of the N.-St. equations, for modelling the fabrication of capillary tubes. The final asymptotic equations are solved numerically and then compared with the N.-St. solutions, obtained with a commercial finite elements solver. The present paper focuses on the comparison of the solution of the two methods taking into account the effects of surface tension and internal hole pressure, since those are of essential importance during drawing. It is shown that the analytical asymptotic method delivers reliable results for practical applications, as long as the inner pressure or the temperature does not exceed too high values. © 2011 IEEE.
UnivIS-Import:2015-03-09:Pub.2011.tech.ITC.stmmec.compar
Keywords: Asymptotic analysis; holey fibres; mathematical modelling; microstructured optical fibres (MOFs); numerical methods; photonic crystal fibres

Dynamic control of higher-order modes in hollow-core photonic crystal fibers - Euser, Tijmen; Whyte, Graeme; Scharrer, Michael; Chen, J. S. Y.; Abdolvand, Amir; Nold, J.; Kaminski, C. F.; Russell, Philip St. John (Optics Express, 2008)
We present a versatile method for selective mode coupling into higher-order modes of photonic crystal fibers, using holograms electronically generated by a spatial light modulator. The method enables non-mechanical and completely repeatable changes in the coupling conditions. We have excited higher order modes up to LP31 in hollow-core photonic crystal fibers. The reproducibility of the coupling allows direct comparison of the losses of different guided modes in both hollow-core bandgap and kagome-lattice photonic crystal fibers. Our results are also relevant to applications in which the intensity distribution of the light inside the fiber is important, such as particle- or atom-guidance.
EAM Import::2019-03-13

Influence of surface tension and inner pressure on the process of fibre drawing - Luzi, Giovanni; Epple, Philipp; Scharrer, Michael; Fujimoto Meinecke, Ken; Rauh, Cornelia; Delgado, Antonio (Journal of Lightwave Technology, 2010)
The present contribution deals with thermofluidynamical features occurring during the drawing of capillaries for microstructured optical fibres. Here, the process stability depends strongly on flow and thermal processes taking place as a preform is heated and drawn in the furnace. This is the case particularly for hollow fibres for which the existence of the inner hole directly depends on material parameters such as the surface tension and the rheological properties and on process parameter such as hole internal pressure and the process temperature. A fluid-mechanics model suggested in the literature that makes use of asymptotic analysis based on small aspect ratio of the micro capillaries, has been revisited and improved recently and the leading-order equations have been then examined in some asymptotic limits by Luzi et al.. Starting from the novel class of solutions of the simplified equations of motion the present paper focuses on the effect of both surface tension and internal hole pressure since those are of essential importance during drawing. Thus, comparisons with experimental data are performed, in order to validate the analytical model developed in , which will be briefly presented here. The theoretical model gives very accurate predictions both when the internal hole is pressurized or when no pressure is applied, as long as the temperature does not reach too high values. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2010.tech.ITC.stmmec.influe
Keywords: Asymptotic analysis; Holey fibres; Micro structured optical fibres (MOFs); Numerical methods; Photonic crystal fibres

Monitoring of catalytic reactions in photonic crystal fiber - Cubillas, Ana Maria; Schmidt, Matthias; Scharrer, Michael; Euser, T. G.; Etzold, Bastian; Taccardi, Nicola; Wasserscheid, Peter; Russell, Philip St. John (2011 Conference on Lasers and Electro-Optics Europe and 12th European Quantum Electronics Conference, CLEO EUROPE/EQEC 2011, 2011)
Hollow-core photonic crystal fiber (HC-PCF) offers several advantages for chemical analysis, for example, long optical pathlengths, sub-L sample volumes, close to 100% overlap between light and sample, and more compact systems for sensing [1-2] and photochemistry [3-4]. Here we compare the performance of a conventional cuvette-based UV-VIS system for monitoring of catalytic reactions with a system based on liquid-filled HC-PCF. We study the photo-Fenton catalytic reaction, which under visible light irradiation induces degradation of methylene blue dye (MB) in the presence of Fe2+ / H2O 2 [5]. © 2011 IEEE.
CRIS-Team Scopus Importer:2023-08-15

Photochemical Microreactors in Photonic Crystal Fibers - Cubillas, Ana Maria; Scharrer, Michael; Euser, Tijmen G.; Schmidt, Matthias; Etzold, Bastian; Taccardi, Nicola; Wasserscheid, Peter; Russell, Philip St. John (OSA Publishing, 2012)
Hollow-core photonic crystal fiber offers new possibilities for sensing and photochemistry applications. In this paper we review our recent achievements on liquid-phase photochemical microreactors using photonic crystal fibers and discuss our future prospects in this field.

Quantitative broadband chemical sensing in air-suspended solid-core fibers - Euser, Tijmen; Chen, J. S. Y.; Scharrer, Michael; Russell, Philip St. John; Farrer, N. J.; Sadler, P. J. (Journal of Applied Physics, 2008)
We demonstrate a quantitative broadband fiber sensor based on evanescent-field sensing in the cladding holes of an air-suspended solid-core photonic crystal fiber. We discuss the fabrication process, together with the structural and optical characterization of a range of different fibers. Measured mode profiles are in good agreement with finite element method calculations made without free parameters. The fraction of the light in the hollow cladding can be tuned via the core diameter of the fiber. Dispersion measurements are in excellent agreement with theory and demonstrate tuning of the zero dispersion wavelength via the core diameter. Optimum design parameters for absorption sensors are discussed using a general parameter diagram. From our analysis, we estimate that a sensitivity increase of three orders of magnitude is feasible compared to standard cuvette measurements. Our study applies to both liquid and gas fiber sensors. We demonstrate the applicability of our results to liquid chemical sensing by measuring the broad absorption peak of an aqueous NiCl2 solution. We find excellent agreement with the reference spectrum measured in a standard cuvette, even though the sample volume has decreased by three orders of magnitude. Our results demonstrate that air-suspended solid-core photonic crystal fibers can be used in quantitative broadband chemical-sensing measurements.
EAM Import::2019-03-12

Resonance amplification of defect emission in ZnO-inverted opal - Khunsin, Worawut; Scharrer, Michael; Aagesen, Larry K.; Anderson, Mark A.; Chang, Robert P. H.; Sotomayor Torres, Clivia M.; Romanov, Sergei G. (Optics Letters, 2009)
Transformation of broadband emission of oxygen defects in the carcass of ZnO-inverted opal into a multiple-mode amplified spontaneous emission band has been observed in the spectral interval of a photonic bandgap upon increasing excitation intensity. The mode structure has been assigned to amplification of emission coupled to resonance modes of the self-selected distributed Bragg resonator. The surprisingly low 2 W/cm^2 onset of amplification has been explained by the long radiative decay time of defect states populated according to the three-level excitation scheme. The decrease of emission intensity between amplified peaks has been associated with the saturation of the ZnO defect emission.
EAM Import::2019-03-13

Ultra-Low Concentration Monitoring of Catalytic Reactions in Photonic Crystal Fiber - Cubillas, Ana Maria; Schmidt, Matthias; Scharrer, Michael; Euser, Tijmen G.; Etzold, Bastian; Taccardi, Nicola; Wasserscheid, Peter; Russell, Philip St. John (Chemistry - A European Journal, 2012)
Photonic crystal fibers as microreactors: Photonic crystal fibers can be used as microreactors (see figure). As an example, the illustration shows the difference in size between a 10cm cuvette (left), and a photonic crystal fiber (right; not to scale).